Techniques For Teaching Reading at The Seventh Grade Of SMP Muhammadiyah 5 Surakarta In 2016/2017 Academic Year - Aziz Suminta Putra, Muhammad, Mauly Halwat Hikmat,Ph.D (2017)
This study is aimed to analyze the techniques used by teacher, the purpose of each technique used, teacher's role and student's role in teaching learning process, the problems faced by the teacher and the teacher's solution to solve problems during teaching learning process. The subjects of this study are an English teacher and 7th grade students of SMP Muhammadiyah 5 Surakarta. Data were taken from observation, interview, and documentation. The data of this study were the techniques for teaching reading, teacher's role, student's role, the teacher's problems and teacher's solution. Techniques for analyzing the data were data reduction, data display, and data verification. The findings of the research showed that techniques used by teacher to develop students' comprehension were silent reading, prediction, and modeling. The purposes of using those techniques were to make students understand the material easily during teaching learning process, to help the students increase their ability, and to improve their knowledge. There were two problems faced by the teacher, namely vocabulary accomplishment and the classroom management. The solution of the problems were giving materials suitable with student's ability and using media in teaching learning process. Keyword: teaching techniques, reading